EFEK VARIASI MASSA DAN ANALISA EFISIENSI BIOMASSA LIMBAH KAYU AKASIA DALAM PENGOLAHAN OPAK SINGKONG MENGGUNAKANKOMPOR BIOMASSA - Juandi Juandi; Ray Afriando; Usman Malik (Prodi Fisika FST UNJA, 2018)
Has conducted research on “Variation Of Mass Effect and Analysis Of The Efficiency Biomass Accacia Timber Waste In Processing Cassavas Opak Using Biomass Stove” using the experimental method. The biomass stoves is using biomass energy from accacia timber waste as an energy source or fuel with a variety of mass 1200 grams, 1000 grams, and 800 grams. The observations were carried out for 60 minutes with intervals of 10 minutes each observation. The research results show that at mass 1000 grams obtained value temperature highest of 4630C. The average rate of heat energy is missing from the third variation mass 800 grams, 1000 grams, and 1200 grams receive is 514.439 Joule/s, and the average rate of energy heat elapsed of 29176.323 Joule/s with the water levels were lost during steaming of 6.046 %, and the average a mass of type the end of 60.287 kg/m3. The efficiency obtained with the values respectively of 99.542 %, 99.270 %, and 99.316 %.